2007
DOI: 10.3923/pjbs.2007.2544.2552
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Canthaxanthin Production by Dietzia natronolimnaea HS-1 Using Response Surface Methodology

Abstract: Sequential methodology combining a screening stage by fractional factorial design and an optimization stage by central composite design was applied to enhance canthaxanthin production of Dietzia natronolimnaea HS-1 in shake flask cultures. Five variables (pH, luminous intensity, inoculum percent, concentration of glucose and concentration of NaCl) were studied with the first design and the results revealed that three factors (pH, concentration of glucose and concentration of NaCl) had greater influence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In recent years, CTX 35 production from biological resources has developed with concerning to restriction of synthetic 36 carotenoids in many industries 3,4 . 38 Dietzia natronolimnaea HS-1 and D. maris NIT-D identified as the best microbial sources in the 39 CTX production in compared to the levels of CTX biosynthesized by Brevibacterium KY-4313, 40 Bradyrhizobium strain ORS278, Haloferax alexandrinus TMT, Micrococcus roseus, Gordonia 41 jacobaea MV-1 and Chlorella zofingiensis [5][6][7][8][9][10][11] . 38 Dietzia natronolimnaea HS-1 and D. maris NIT-D identified as the best microbial sources in the 39 CTX production in compared to the levels of CTX biosynthesized by Brevibacterium KY-4313, 40 Bradyrhizobium strain ORS278, Haloferax alexandrinus TMT, Micrococcus roseus, Gordonia 41 jacobaea MV-1 and Chlorella zofingiensis [5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, CTX 35 production from biological resources has developed with concerning to restriction of synthetic 36 carotenoids in many industries 3,4 . 38 Dietzia natronolimnaea HS-1 and D. maris NIT-D identified as the best microbial sources in the 39 CTX production in compared to the levels of CTX biosynthesized by Brevibacterium KY-4313, 40 Bradyrhizobium strain ORS278, Haloferax alexandrinus TMT, Micrococcus roseus, Gordonia 41 jacobaea MV-1 and Chlorella zofingiensis [5][6][7][8][9][10][11] . 38 Dietzia natronolimnaea HS-1 and D. maris NIT-D identified as the best microbial sources in the 39 CTX production in compared to the levels of CTX biosynthesized by Brevibacterium KY-4313, 40 Bradyrhizobium strain ORS278, Haloferax alexandrinus TMT, Micrococcus roseus, Gordonia 41 jacobaea MV-1 and Chlorella zofingiensis [5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…A 209 water bath (45°C) was also used to completely extract the pigments6 . Finally, the flasks to produce CTX 187 were incubated in an orbital shaking incubator (Model JEIO TEC SI-4000R, Korea) at 180 rpm 188 and 28±2°C for 6 days used to inoculate the bioreactor (Fig.…”
mentioning
confidence: 99%
“…Temperature is one of the most important environmental factors affecting the growth of microorganisms and it causes changes in many biosynthetic pathways, such as carotenoid biosynthesis [14]. The Paracoccus beibuensis shows highest pigment produced was at 30 0 C and it was found that as the temperature increases there is increase in biomass but pigment production was reduced (Figure 4).…”
Section: Optimization Of Temperaturementioning
confidence: 98%
“…The optimum aeration intensity of D. natronolimnaea HS-1 and Chlorococcum sp. The highest growth rate and cell concentration in CX-containing microorganisms, such as D. natronolimnaea HS-1 (1000 Lux) and C. emersonii (300 μmol/m 2 s), were obtained at higher light intensity [16,45,68]. The production and accumulation of carotenoid by D. natronolimnaea HS-1 and Dunaliella sp.…”
Section: Carbon and Nitrogen Sourcesmentioning
confidence: 99%
“…Nonetheless, the level of intensity and protocol of illumination required for the high production of carotenoids change according to the type of microorganism in the fermentation media. The highest growth rate and cell concentration in CX-containing microorganisms, such as D. natronolimnaea HS-1 (1000 Lux) and C. emersonii (300 μmol/m 2 s), were obtained at higher light intensity [16,45,68]. More researchers also reported that the levels of high irradiation led to increase the synthesis of other carotenoids by the green alga H. pluvialis (125 μmol/m 2 s) and Phaffia rhodozyma (500 Lux) [20,33].…”
Section: Temperature Ph Aeration and Illuminationmentioning
confidence: 99%